BARRIERS AND SUCCESS FACTORS FOR DEVELOPING A LEAN CULTURE A case study at a Romanian contractor - BAHNARIU, BOGDAN (My University, 2018)
After proving its benefits in the manufacturing industry, Lean management has been introduced into the construction industry as a response to its problems regarding low efficiency, productivity and overall performance. However, many construction companies have struggled to implement Lean, considering it a very complex and confusing philosophy. Applying Lean tools and techniques without proper consideration of the human dimension is destined to failure, as ‘people’ are one of the key success factors when undertaking a Lean journey. Therefore, the aim of this thesis was to study the barriers and success factors which would allow to develop and implement the Lean culture necessary to enable Lean management tools. The work environment at a Romanian construction company was studied in the light of Lean management tools and cultural prerequisites, in order to assess the company’s capacity to adapt to Lean management. The results showed that the Romanian company in the study partially satisfied some of the requirements necessary for a Lean culture, the most important being its focus on its employees’ development, which has also created a good work environment based on trust and respect. The employees showed good theoretical knowledge and a high level of skills and expertise, but a lack of rules, procedures and long-term vision were among the most important problems which the company would have to be overcome. Another identified barrier for developing a Lean culture was the absence of a culture for safety, organisation or standardised processes, which could be overcome by implementing clear rules, procedures and work standardisation, with a close follow up of their application. In this way the company could succeed in developing a Lean culture which would adhere to Lean management tools and principles.
Keywords: Samhällsbyggnadsteknik; Civil Engineering